Serum Concentrations of Fibroblast Growth Factor 19 in Patients With Obesity and Type 2 Diabetes Mellitus: the Influence of Acute Hyperinsulinemia, Very-Low Calorie Diet and PPAR-α Agonist Treatment - MRÁZ, M.; LACINOVÁ, Z.; KAVÁLKOVÁ, P.; HALUZÍKOVÁ, D.; TRACHTA, P.; DRÁPALOVÁ, J.; HANUŠOVÁ, V.; HALUZÍK, M. (Physiological research, 2011)
The aim of our study was to measure serum concentrations of fibroblast growth factor 19 (FGF-19) in patients with obesity (OB), obesity and type 2 diabetes mellitus (T2DM) and healthy subjects (C) at baseline and after selected interventions. We measured serum FGF-19 levels and other biochemical and hormonal parameters in 29 OB and 19 T2DM females and 30 sex- and age-matched control subjects. The interventions were acute hyperinsulinemia during isoglycemic-hyperinsulinemic clamp (n=11 for T2DM and 10 for C), very-low calorie diet (VLCD, n=12 for OB) and 3 months treatment with PPAR-α agonist fenofibrate (n=11 for T2DM). Baseline serum FGF-19 levels were significantly lower in OB relative to C group (132.1±12.7 vs. 202.2±16.7 pg/ml, p<0.05), while no significant difference was observed between T2DM and OB or control group. Acute hyperinsulinemia tended to decrease FGF-19 levels in both healthy and T2DM subjects. Three weeks of VLCD in OB group had no significant effect on FGF-19, whereas three months of fenofibrate treatment markedly reduced FGF-19 levels in T2DM patients (194.58±26.2 vs. 107.47±25.0 pg/ml, p<0.05). We conclude that FGF-19 levels in our study were at least partially dependent upon nutritional status, but were not related to parameters of glucose metabolism or insulin sensitivity.